Effects of mold temperature on the microstructure and tensile properties of SiCp/2024 Al-based composites fabricated via powder thixoforming. (15th December 2016) - Li, P.B.; Chen, T.J.; Qin, H.
Abstract: In this study, the effects of mold temperature on the microstructure and tensile properties of 2024 Al-based composites reinforced with SiC particles (SiCp ; 10 vol.%) and fabricated via powder thixoforming were investigated. The tensile properties of the composite were dependent upon the mold temperature because it affected the secondary solidification behavior, compactness of the secondary solidified structures, dislocation density introduced by the plastic deformation that occurs during thixoforming, and recrystallization behavior. The tensile properties of the composite that was thixoformed at 350 °C exhibited the largest improvements, with the ultimate tensile strength (UTS) increasing by 235.4% (UTS = 379 MPa) and elongation decreasing by 31.0% (elongation = 4.0%) compared to those of the as-cast 2024 alloy. The increased UTS was ascribed to the thermal-mismatch and load-transfer strengthening mechanisms, enhanced compactness, increased dislocation density, decreased grain size, and lower concentration of the deleterious θ-phase. The fracturing of the composites was caused by the cracking and debonding of the SiCp as the mold temperature increased, which in turn led to the total matrix failure. Graphical abstract: Highlights: Powder thixoforming technology exhibits superiority for fabricating SiCp /2024 composites. Increasing mold temperature enhances compactness and deformation degree and decreases the concentration of θ-phase. The best ultimate tensile strength of 379 MPa is achieved at mold temperature of 350 °C. The cracking and debonding of the SiCp become predominant as the mold temperature increases.